Pengaruh Perceived Usefulness pada Virtual Try-On, Online Customer Review dan Brand Trust terhadap Purchase Decision Produk Kosmetik L’oreal Paris di Shopee - Vio Andira Suprayitno; Nadya Fadillah; Rizka Zakiah (Indo Publishing, 2026)
reviews, and brand trust on the purchase decision of L'Oreal Paris cosmetic products on Shopee. This research employed a quantitative method with data collected through a questionnaire. The population consisted of Generation Z Shopee users residing in the Special Capital Region of Jakarta (DKI Jakarta). The sampling technique used was non-probability sampling with a purposive sampling method, resulting in 180 respondents. The data were analyzed using multiple linear regression analysis, including descriptive statistical analysis, instrument testing, classical assumption tests, multiple linear regression analysis, hypothesis testing (t-test), and the coefficient of determination (R²), with the assistance of SPSS version 32. The results indicate that perceived usefulness in virtual try-on, online customer reviews, and brand trust each have a positive and significant effect on purchase decisions, with brand trust being the most dominant influencing variable. Therefore, optimizing virtual try-on features, effectively managing online customer reviews, and strengthening brand trust can serve as effective digital marketing strategies to enhance consumers' purchase decisions for L'Oreal Paris cosmetic products on the Shopee platform.